A new facility for proton radiobiology at the Trento proton therapy centre: Design and implementation. (February 2019) - Tommasino, Francesco; Rovituso, Marta; Bortoli, Eleonora; La Tessa, Chiara; Petringa, Giada; Lorentini, Stefano; Verroi, Enrico; Simeonov, Yuri; Weber, Ulrich; Cirrone, Pablo; Schwarz, Marco; Durante, Marco; et al.
Highlights: New experimental facility for research in the field of proton radiobiology. Passive scattering setup for large field irradiation (up to 16 cm diameter). Pristine Bragg peak or spread-out Bragg peak (SOBP). Full geometry of the irradiation setup implemented in the Monte Carlo code Geant4. Abstract: We present a new facility dedicated to radiobiology research, which has been implemented at the Trento Proton Therapy Centre (Italy). A dual-ring double scattering system was designed to produce irradiation fields of two sizes (i.e. 6 and 16 cm diameter) starting from a fix pencil beam at 148 MeV. The modulation in depth was obtained with a custom-made range modulator, optimized to generate a 2.5 cm spread-out Bragg peak (SOBP). The resulting irradiation field was characterized in terms of lateral and depth-dose profiles. The beam characteristics and the geometry of the setup were implemented in the Geant4 Monte Carlo (MC) code. After benchmark against experimental data, the MC was used to characterize the distribution of dose-average linear energy transfer (LET) associated to the irradiation field. The results indicate that dose uniformity above 92.9% is obtained at the entrance channel as well as in the middle SOBP in the target regions for both irradiation fields. Dose rate in the range from 0.38 to 0.78 Gy/min was measured, which can be adjusted by proper selection of cyclotron output current, and eventually increased by about a factor 7. MC simulations were able to reproduce experimental data with good agreement. The characteristics of the facility are in line with the requirements of most radiobiology experiments. Importantly, the facility is also open to external users, after successful evaluation of beam proposals by the Program Advisory Committee.